EVALUATION OF IMPLEMENTATION OF SCHOOL / MADRASAH ACCREDITATION PROGRAMS IN PALEMBANG CITY IN SOUTH SUMATRA PROVINCE 2018 - Dewi Astenia; Rugaiyah Rugaiyah; Neti Karnati (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of the study was to evaluate the implementation of the School/ Madrasah accreditation program at the SMA/SMK/MA level in Palembang City. This study uses an implementation of the public policy model by George Edward lll, namely: communication, resources, dispositions, bureucratic structure. Data collection techniques used are documentation, interviews and observation. The data analysis technique used is the technique of Miles and Huberman, analysis activities consist of three activities or processes that occur simultaneously namely: data reduction, data display and conclusion drawing/verification. The results of the study show: 1) The communication component is carried out through activities: a) BAP-S/M Provincial coordination meeting with UPA-S/M District /City is carried out properly in accordance with the objectives. b) Training on renewal of accreditation assessors to meet the needs of trustworthy and competent assessors has been achieved well c) Seminar on the results of accreditation implementation that socializes the results of the implementation of accreditation to stakeholders in the area concerned, regarding the status of school / madrasah accreditation about rank A, B, C , and Not Accredited has been implemented and achieved. d) Dissemination and the introduction of school/madrasah accreditation to the dissemination of information in the form of a directory, to schools/madrasas has been carried out but is still not maximally up to the target. 2). the resources used to support the success of the school/madrasah accreditation program in the implementation of accreditation programs include: a) Facilities and infrastructure needed for the implementation of school/madrasah accreditation are not sufficiently equipped for the accreditation needs of schools/madrasas properly. b) Sources of funds for implementing activities in financial management, financial reporting and financial accountability reports are clear and correct. c) Human resources assessors, school accreditation teams and secretariat staff have carried out their duties and functions well and smoothly. 3)Disposition of policy implementers of accreditation activities work with full awareness and are oriented to guidelines and rules are implemented well. 4) The bureaucratic structure of accreditation activities through monitoring and evaluating the performance of BAP-S/M and the BAP-S/M secretariat on the implementation of accreditation programs has been carried out and is still not yet optimal. Keywords: evaluation, school/madrasah accreditation program.